2015
DOI: 10.2172/1227265
|View full text |Cite
|
Sign up to set email alerts
|

Western Wind and Solar Integration Study Phase 3A: Low Levels of Synchronous Generation

Abstract: Leading into this study, WWSIS-3 delved into the dynamic performance of the grid in the fractions of a second to 1 min following a large disturbance (e.g., loss of a large power plant or a major transmission line), which is critical to system reliability. In particular, that study examined the large-scale transient stability and frequency response of the Western Interconnection with high penetrations of wind and solar, and it identified means to mitigate any adverse performance impacts via transmission reinfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…In recent years, modern wind turbines and PV systems have demonstrated their ability, if either required to or compensated by markets, to provide similar reliability services historically only provided by synchronous generators, including the provision of automatic generation control, primary frequency response, as well as synthetic inertia CAISO 2017a). Within the limits of the studies, detailed grid simulations (Miller et al 2014;Miller, Leonardi, and D'Aquila 2015) have concluded that with appropriate planning and engineering, systems with high VRE penetrations are able to maintain the same level of reliability that already exists in the U.S. power system.…”
Section: Text Box 1 Grid Integration Of Variable Renewable Energymentioning
confidence: 98%
“…In recent years, modern wind turbines and PV systems have demonstrated their ability, if either required to or compensated by markets, to provide similar reliability services historically only provided by synchronous generators, including the provision of automatic generation control, primary frequency response, as well as synthetic inertia CAISO 2017a). Within the limits of the studies, detailed grid simulations (Miller et al 2014;Miller, Leonardi, and D'Aquila 2015) have concluded that with appropriate planning and engineering, systems with high VRE penetrations are able to maintain the same level of reliability that already exists in the U.S. power system.…”
Section: Text Box 1 Grid Integration Of Variable Renewable Energymentioning
confidence: 98%
“…The WECC power system has a peak demand of approximately 150 GW. Studies have been conducted to examine the impacts of high levels of VRE in the WECC [35]. These studies have shown that 35% on an annual basis and 65% on an instantaneous basis are technically possible.…”
Section: Examples Of Vre Penetrations In Power Gridsmentioning
confidence: 99%
“…Besides maintaining the loadsupply equilibrium at all times, the power grid operators must also have the capability of restoring the stability of the grid in short intervals (in 10-20 seconds) after disturbances. The aforementioned capability is referred to as transient stability, as typically visualized in a diagram like Figure 8b [33], where masses represent generators, strings transmis- [34] with a water distribution analogy, adjusts the power production levels of generators automatically in response to load changes or disturbances. AGC is a ripe target for attack that may result in a significant operational damage and instability [35].…”
Section: A Power Grid Applicationsmentioning
confidence: 99%
“…The delicate and precarious balance and operating conditions of the power grid, as shown at a high level analogy in Figure 8b, may easily lead to activation of a series of protection mechanisms with cascading failures and largescale blackouts [38], [39], such as the blackouts of 1965 in Northeast America, 1978 in France, 1999 in Brazil, 2003 in northeastern US and Canada [40], 2012 in India [41], etc. In addition to the accidental disruption to power, there have been intentional disruptions as a result of general cyberattacks, as summarized in FIGURE 8: (a) A simplified representation of the Automatic Generation Control (AGC) in the power grid [34], (b) A metaphorical illustration of the concept of transient stability in the power grid [33].…”
Section: A Power Grid Applicationsmentioning
confidence: 99%